MAINTENANCE SELANG ATAU JARUM (VIBRATION NEEDLE) PADA MESIN VIBERATOR INTERNAL PT. WKB - Bagas Dwi Prayoga (ELEMEN : JURNAL TEKNIK MESIN, 2026)
The maintenance of hoses or needles (vibration needles) in internal vibrators is crucial to ensure the quality of concrete production at PT. WKB. The main issue addressed in this internship report is the frequent damage to vibration hoses, which reduces work efficiency. The purpose of this activity is to understand the proper maintenance methods to extend the equipment's service life. The methods used include field observations, literature studies, and interviews with technicians. The findings show that breakdown maintenance is still predominantly applied, with common damages such as wear on the flexible shaft and needle head. Routine maintenance, such as lubrication, cleaning, and checking connections, can significantly reduce the frequency of breakdowns. In conclusion, consistent application of preventive maintenance improves the reliability of internal vibrators and supports the smooth production of precast concrete.